Solitary occipital bone plasmacytoma with unusual ocular signs (Ukrainian Journal of Ophthalmology, 2023)
Solitary occipital bone plasmacytoma at the level of the confluence of sinuses is a rare condition. We report a case of an unusual combination of occipital bone plasmacytoma, ocular motility abnormalities, and papilledema. To the best of our knowledge, no case has been reported in the literature on such a combination of nosology, location and clinical course.